2011
DOI: 10.1158/1541-7786.mcr-10-0344
|View full text |Cite
|
Sign up to set email alerts
|

miR-15 and miR-16 Are Direct Transcriptional Targets of E2F1 that Limit E2F-Induced Proliferation by Targeting Cyclin E

Abstract: microRNAs (miR) are small noncoding RNA molecules that have recently emerged as critical regulators of gene expression and are often deregulated in cancer. In particular, miRs encoded by the miR-15a, miR-16-1 cluster seem to act as tumor suppressors. Here, we evidence that the miR-15a, miR-16-1 cluster and related miR-15b, miR-16-2 cluster comprise miRs regulated by E2F1, a pivotal transcription factor that can induce both proliferation and cell death. E2F1 is a critical downstream target of the tumor suppress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 43 publications
4
149
1
3
Order By: Relevance
“…Previously, it has been reported that members of the miR-15 family are under the direct transcriptional control of E2F1 (ref. 24), a transcription factor best known for its regulation of the gene expression programme required for cell cycle progression. E2F1 binds to the promoters of DLEU2 and SMC4 genes leading to increased expression of the miRNAs that are processed from these genes.…”
Section: Screening For Mirnas Controlling Salmonella Infectionmentioning
confidence: 99%
“…Previously, it has been reported that members of the miR-15 family are under the direct transcriptional control of E2F1 (ref. 24), a transcription factor best known for its regulation of the gene expression programme required for cell cycle progression. E2F1 binds to the promoters of DLEU2 and SMC4 genes leading to increased expression of the miRNAs that are processed from these genes.…”
Section: Screening For Mirnas Controlling Salmonella Infectionmentioning
confidence: 99%
“…Similarly, up regulation of mir-17-92 and miR-21 by targeting PTEN (phosphatase and tensin homolog protein act as a tumour suppressor gene in the regulation of the cell cycle) and inhibit expression of the transcription factor E2F1, whereby miR-221/222 up regulation are targeting p27Kip1 (a cell-cycle regulatory protein that interacts with cyclin-CDK2/-CDK4) and inhibiting cell cycle progression at G1, promote cellular proliferation and are capable of up regulating the components of the apoptotic signalling pathway and transforming to cancer cells resistant or susceptible to extrinsic factors at the same checkpoint (Petrocca et al, 2008). Conversely, oncogenic miRNA; miR-15a, miR-16-1 cluster and related miR-15b, miR-16-2 cluster in CLL patients regulated by E2F1 (a critical downstream target of the pRB) often inactivated in human tumours resulting in dysregulation of E2F activity which have been reported that reduces the levels of cyclin D1, cyclin D3, cyclin E1, and CDK6 was triggers an accumulation of multiple cell cycle-promoting genes and was predicted that both miRNAs contribute to apoptosis by decreasing the levels of the apoptotic inhibitor Bcl-2 at G1/S phase (Ofir et al, 2011). Recent findings determine that knockdown of microRNA-34a decreased the rate of apoptosis caused by PRIMA-1 which is a small molecule that restores tumour suppressor function to mutant p53 to induced apoptosis in the cell cycle (Duan et al, 2010).…”
Section: Mirnas In Cell Cycle Regulationmentioning
confidence: 99%
“…Noncoding RNA encompass a variety of discrete entities, including micro RNA (miRNA), ultra conserved long non-coding RNA and pyknons. While several miRNA species are regulated via E2F and RB, the mechanisms coordinating such altered expression of miRNA, [11][12][13][14] the targets and overall mode of regulation has remained obscure relative to coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] For example, deregulated miRNA expression has been implicated in aberrant proliferation, genome stability and epithelial-mesenchymal transition. [17][18][19] Analyses of miRNA expression in breast cancer tumor specimens have demonstrated association with specific breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%